The combined effects of reactant kinetics and enzyme stability explain the temperature dependence of metabolic rates. Issue 11 (23rd April 2017) - DeLong, J. P.; Gibert, J. P.; Luhring, T. M.; Bachman, G.; Reed, B.; Neyer, A.; Montooth, K. L.
Abstract: A mechanistic understanding of the response of metabolic rate to temperature is essential for understanding thermal ecology and metabolic adaptation. Although the Arrhenius equation has been used to describe the effects of temperature on reaction rates and metabolic traits, it does not adequately describe two aspects of the thermal performance curve (TPC) for metabolic rate—that metabolic rate is a unimodal function of temperature often with maximal values in the biologically relevant temperature range and that activation energies are temperature dependent. We show that the temperature dependence of metabolic rate in ectotherms is well described by an enzyme‐assisted Arrhenius (EAAR) model that accounts for the temperature‐dependent contribution of enzymes to decreasing the activation energy required for reactions to occur. The model is mechanistically derived using the thermodynamic rules that govern protein stability. We contrast our model with other unimodal functions that also can be used to describe the temperature dependence of metabolic rate to show how the EAAR model provides an important advance over previous work. We fit the EAAR model to metabolic rate data for a variety of taxa to demonstrate the model's utility in describing metabolic rate TPCs while revealing significant differences in thermodynamic properties across species and acclimation temperatures. Our model advances our ability to understand the metabolic and ecological consequences of increases in the mean and variance of temperature associated with global climate change. In addition, the model suggests avenues by which organisms can acclimate and adapt to changing thermal environments. Furthermore, the parameters in the EAAR model generate links between organismal level performance and underlying molecular processes that can be tested for in future work. Abstract : We modify the Arrhenius function for the dependence of metabolic rate on temperature to include the effects of temperature‐dependent enzyme function on the activation energy of metabolic reactions. The resulting enzyme‐assisted Arrhenius (EAAR) model is consistent with the unimodal shape of metabolic rate data. We also show how the EAAR model can facilitate greater understanding of thermal adaptation by linking the thermodynamic properties of enzymes to whole‐organism performance.